2018
DOI: 10.1155/2018/4934890
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological Properties of the Medical Maggot: A Novel Therapy Overview

Abstract: In the last decade, maggot has been hailed as the miraculous “medicinal maggot” for its diverse properties, including antimicrobial, antibiofilm, anti-inflammatory, and wound healing activities. The fact that maggots show so many beneficial properties has increased the interest in these tiny larvae dramatically. Whilst there is relatively abundant clinical evidence to demonstrate the success of maggots as debridement agents, not so much emphasis has been placed on the basic science evidence, which was a combin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
43
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(47 citation statements)
references
References 69 publications
0
43
0
4
Order By: Relevance
“…The larval ES has exhibited antimicrobial activity against both Gram-positive and Gram-negative bacteria (Bexfield et al, 2008;Yan et al, 2018), as well as against protozoan parasites causing dermal leishmaniasis (Polat et al, 2012;Sanei-Dehkordi et al, 2016). Thus, suppressing the pathogenic microbes on the feeding substrates promotes the larval development and survival (Sherman et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…The larval ES has exhibited antimicrobial activity against both Gram-positive and Gram-negative bacteria (Bexfield et al, 2008;Yan et al, 2018), as well as against protozoan parasites causing dermal leishmaniasis (Polat et al, 2012;Sanei-Dehkordi et al, 2016). Thus, suppressing the pathogenic microbes on the feeding substrates promotes the larval development and survival (Sherman et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…The use of larvae of dipterous flies or maggots for the treatment of wounds is based on multitude of observations since antiquity. The technique was applied in American civil war and during the First World War and was later approved by the FDA in 2004 for use in humans (Yan et al 2018;Bazaliński et al 2019). This form of natural, relatively cheap, and effective therapy is used for the treatment of diabetic ulcers, venous ulcers, traumatic and postsurgical wounds, osteomyelitis, and burns (El-Tantawy 2015).…”
Section: Antibacterial Activity Of Arthropodsmentioning
confidence: 99%
“…Moreover, Cazander et al (2009) studied the formation of biofilms by other bacteria (Staphylococcus aureus, S. epidermidis, Klebsiella oxytoca, Enterococcus faecalis, and Enterobacter cloacae) on several biomaterials (polyethylene, titanium, and stainless steel) and demonstrated that ES products of maggots can interfere with biofilm formation and provide a novel treatment for biofilm formation on contaminated biomaterials (Cazander et al 2009). These effects can be attributed to the interruption of protein adhesion-mediated biofilm formation and digestion of DNA in biofilms (Yan et al 2018).…”
Section: Antibacterial Activity Of Arthropodsmentioning
confidence: 99%
“…Maggot therapy (MT) is one form of animal-based treatment options known as Biotherapy (medicinal use of live organisms) which includes also those of the honey bee (Apitherapy),leech (Hirudotherapy), fish (Ich thiotherapy), worm (Helmitherapy), pets (Animal-assisted therapy) and Phage (Microbialtherapy). Maggot therapy "Larva therapy, Biosurgery or Maggot debridement therapy (MDT)" is the medical use of live maggots for cleaning human chronic and non-healing wounds or certain wounds that are not amenable to other forms of therapy (Sherman et al, 2000;Church and Courtenay, 2002;Tantawi et al, 2007Tantawi et al, & 2010Gupta, 2008;Hall, 2010;Marineau et al, 2011;Sherman, 2014a;Naik andHarding, 2017 andYan et al, 2018). It involves allowing maggots of certain species of blowflies (Family: Calliphoridae)…”
Section: Introductionmentioning
confidence: 99%
“…to consume the necrotic tissue in the wound, and to produce antibiotic substances that kill the pathogenic bacteria and promote tissue healing (Sherman et al, 2000;Nigam et al, 2006a & b;Tantawi et al, 2010 andYan et al, 2018). MT is also used for veterinary purposes.…”
Section: Introductionmentioning
confidence: 99%